Economic and institutional factors affecting real property tax collection in the National Capital Region - Uy, Maria Teresa D. (Philippine Journal of Public Administration; Vol 65 No 1&2 (2021), 2021)
The study assessed the effect of economic development, internal revenue allotment (IRA), and tax administration on the real property tax (RPT) collection of local government units (LGUs) in the National Capital Region (NCR) using a multivariate regression analysis based on relevant panel data from CY 2014-2018. The study found that local economic development has a negative influence and IRA has a positive effect on RPT collection. The significant relationships between proxy variables for tax administration (i.e., government efficiency index and number of SMV revisions due) and RPT collection serve as the salient findings of the study. Government efficiency index positively affects RPT collection, while the non-revision of schedule of market values (SMVs) negatively affects RPT collection. RPT has a great potential in terms of providing a stable revenue source for local governments and introduction of tax administration reforms and their proper implementation will give LGUs greater fiscal autonomy, which may lead to a genuine and meaningful self-governance. Keywords: real property tax collection; local economic development; internal revenue allotment; tax administration